Monitoring near-riverbed sediment behavior of debris flows using hydrophones - Suzuki, Takuro; Hasegawa, Yuji; Mizuno, Hideaki; Osanai, Nobutomo (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"Hydrophones are steel pipes containing a microphone, and they can be used to measure bedload transport intensity. Bedload discharge and average grain diameter can be calculated analytically using sound pressure data. In this study, hydrophones were used to identify debris flows. The proportional relationship between the output voltage corresponding to a grain collision and its momentum was used to analyze electric pressure distribution, which was then used to calculate the mean diameter of colliding grains. Flume experiments were conducted to verify the effectiveness of this method in recognizing the time change of the near-river- bed sediment discharge from debris flows and low concentrated flows, including their transition ranges. Total sediment discharge can also be calculated if the collision rate upon the hydrophones is evaluated by setting the interface. In addition, the time change of the average grain diameter can be calculated. Large grains were detected in the debris flow surge, and the analytic values were in rough agreement with the experimental values."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Hydrophones are steel pipes containing a microphone, and they can be used to measure bedload transport intensity. Bedload discharge and average grain diameter can be calculated analytically using sound pressure data. In this study, hydrophones were used to identify debris flows. The proportional relationship between the output voltage corresponding to a grain collision and its momentum was used to analyze electric pressure distribution, which was then used to calculate the mean diameter of colliding grains. Flume experiments were conducted to verify the effectiveness of this method in recognizing the time change of the near-river- bed sediment discharge from debris flows and low concentrated flows, including their transition ranges. Total sediment discharge can also be calculated if the collision rate upon the hydrophones is evaluated by setting the interface. In addition, the time change of the average grain diameter can be calculated. Large grains were detected in the debris flow surge, and the analytic values were in rough agreement with the experimental values.